Specific dynamics for the Domain-Walls in Einstein-Maxwell-Dilaton theory - Mazharimousavi, S. Habib; Halilsoy, Mustafa (Classical and Quantum Gravity, Institute of Physics (IOP) Publishing, 2012)
We consider Einstein-Maxwell-Dilaton (EMD) Lagrangian supplemented by double Liouville potentials to enrich our system and investigate the resulting dynamics. The general solution provides us alternative structures induced on the 3-dimensional domain wall (DW) moving in the 4-dimensional bulk. In particular, the local maximum in the potential suggests a maximum bounce (or onset for a contraction phase) of the 3-dimensional Friedmann-Robertson-Walker (FRW) universe on the DW. Depending on the choice of parameters we plot various cases of physical interest.
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1088/0264-9381/29/6/065013) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: gravity; Einstein-Maxwell-Dilaton theory; general relativity